Poster 214: Posterior Tibial Slope Reducing Osteotomy in Complex Revision Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2022) - Thomassen, Stephan; Winkler, Philipp; Lucidi, Gian Andrea; Firth, Andrew; Musahl, Volker; Getgood, Alan; Vivacqua, Thiago
Objectives: The purpose of this study was to report indications, early radiologic and clinical outcomes, and postoperative complications after closing wedge slope reducing proximal tibial osteotomy, performed in a complex group of patients with failed ACLR in two academic referrals centers in North America. Methods: A retrospective review of patient medical records was performed at two academic referral centers in North America between October and December 2020. Demographic, radiological, and surgical data were collected on a consecutive series of patients who underwent a closing wedge proximal tibial osteotomy to reduce PTS associated with ACLR failure. Approval for this study was obtained by the institutional review boards of the University of Pittsburgh (No.: STUDY20050226) and the University of Western Ontario (No.: 101533). Written informed consent was obtained from all included patients. Patients were identified from a previous database which included a retrospective two-center sample that underwent R-ACLR between 2010 and 2020 performed by two knee surgeons at the University of Pittsburgh and the University of Western Ontario. The final sample included patients who underwent slope reduction with or without associated coronal alignment correction associated with R-ACLR (n=17). Concomitant procedures such as meniscectomy, meniscal repair, lateral extra-articular tenodesis (LET), meniscal allograft transplantation (MAT), re-operations, and complications were described. Data collection was performed by three orthopedic fellows. R-ACLR was performed in a one-stage or two-stage procedure based on the previous tunnel positions, tunnel widening, and surgeon preferences. In the case of two-stage revision, tibial slope reduction osteotomy was performed as the first stage associated with bone grafting of the tibial and/or femoral tunnel. The tibial slope was corrected using a supra-tubercle anterior closing wedge (ACW) proximal tibial osteotomy (PTO) in 16 patients (Neyret et al 2000) and with a complete tibial tubercle osteotomy (TTO) in one case (Bertrand et al 2014) (Figure 1 ). Osteotomies were stabilized using Richards regular fixation staples ® (Smith & Nephew) or the TOMOFIX ® osteotomy system (DePuy Synthes) was used. Techniques were based on the surgeon's preference. Concomitant LET was performed in patients with a grade III positive pivot shift test during examination under anesthesia. PTS and ATT were calculated using a load-bearing lateral x-ray pre-and postoperatively at end of follow-up (Dejour & Bonnin 1994). Patella height was measured in the lateral view using the Caton Deschamps Index (CDI) (Caton et al. 1982). All radiologic measurements were performed by two orthopedic clinical fellows. For assessment of patient-reported outcome the Knee Injury and Osteoarthritis Outcome Score (KOOS) and the International Knee Documentation Committee (IKDC), Subjective Knee Form were collected at final follow up. Results: Of the seventeen patients identified, 53% (9/17) were male with a mean Body-Mass-Index (BMI) of 25.6 (range 20-40; SD: 8.6). The mean clinical and radiologic follow-up was 31.2 months (range 4-84; SD: 24.37). The mean age at the last R-ACLR was 27.7 years old (range 17-52; SD: 9.82). A re-revision of ACLR was performed in the majority of cases (70.6%). A two-stage revision was performed in seven patients (41.2%) with the R-ACLR completed after bone healing was confirmed (range of 5-11 months). Five (29.4%) had a biplanar closing wedge osteotomy to address associated coronal plane malalignment. Quadriceps tendon (QT) autograft was the most common graft at the revision ACLR (8 patients: 47%). Reoperations were necessary for eight patients (47.2%) due to symptomatic hardware, chondral debridement, and postoperative arthrofibrosis. One patient with two previous re-revision ACLRs developed complex regional pain syndrome (CRPS). Graft failure was defined in the event of a high-grade pivot-shift (≥ grade II) during clinical follow-up. A traumatic ACL graft failure occurred in one patient, 27 months post-surgery and a non-traumatic failure was diagnosed in one patient leading to 11.8% of graft failure. Concomitant treatment, alignment correction, and postoperative complications are summarized in table 1. Posterior tibial slope was significantly reduced from the preoperative to postoperative radiographs (mean ± standard error (SE) = 13.9° ± 0.5 vs. 5.3° ± 1.2; p = 0.000(z=3.63)). The CDI showed that patella height was not significantly altered after the PTS correction (mean ± SE = 1.1 ± 0.6 vs. 1.2 ± 0.4, p = 0.11). The intraclass correlation showed an excellet intra-rater agreement and good to excellent inter-rate agreement for the PTS meansurement (ICC: 0.92 to 0.98; ICC: 0.88 to 0.99). Regarding the CDI, the intraclass correlation showed a good to excellent intra-rater agreement and excellent inter-rate agreement (ICC: 0.83 to 0.99; ICC: 0.93 to 0.99). A satisfactory and significant improvement of the ATT among 88.2% of the patients was identified at the last follow-up (mean ± SE = 11.17 ± 4.42 vs. 5.66 ± 4.53, p = 0.02). An excelent inter-rater and intra-rater reliability was achieved ICC (3, 1) = 0.99 (CI: 0.97 to 1.00; 0.98 to 1.00) regarding the ATT measurement (Table 2 ). Patient reported outcomes were completed in nine patients (53%) with a mean of 37.6 months follow-up (range 6-84: SD: 26.8) (table 3 ). Conclusions: Proximal tibial closing wedge osteotomies are an effective surgical approach to correct PTS and ATT in patients after ACLR failure, resulting in a reduction in anterior tibial translation and satisfactory graft survivorship in a complex patient population. Unsatisfactory clinical outcomes are likely related to patients undergoing multiple surgeries and therefore patients should be appropriately counseled in regard to expected outcomes. Figure 1. Preoperative PTS analysis (A). Postoperative PTS reduction osteotomy performed associated to ACL-R (B). Table 1. Surgical data and postoperative complications.